POPULASI DAN INTENSITAS SERANGAN Paraeucosmetus pallicornis PADA TANAMAN PADI DI KABUPATEN MINAHASA SELATAN - Kaparang, Christian L.; Pelealu, Jantje; Salaki, Christina L. (Universitas Sam Ratulangi, 2011)
ABSTRACT The study aimed to determine the population and attacking intensity of Paraeucosmetus pallicornis on rice based on the altitude in South Minahasa regency. Stratified sampling method was conducted consisting of three strata namely 0-300 meters above sea level, >300-600 meters above sea level, and >600 meters above sea level. Sampling was collected by taking the diagonal of each 10 clump at different levels of plant age. The results showed that the highest average populations density of P. pallicornis was found at altitude >600 m above sea level. That was equal to 6.46 individuals per clump. In the altitude of 0-300 meters above sea level, average populations density was 6.07 individuals per clump. The lowest population was detected at altitude >300-600 meters above sea level which was 6.03 individuals per clump. The attacking intensity of P. pallicornis was the highest at an altitude of 0-300 meters above sea level that is equal to 25.87 % per clump, followed by the altitude >300-600 meters above sea level which was 24.12 % per clump. The lowest was an altitude of >600 meters above sea level 23.77 % which was per clump. Keywords: rice, Paraeucosmetus pallicornis